2021
DOI: 10.1007/s12572-021-00298-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural network-based anomalous diffusion parameter estimation approaches for Gaussian processes

Abstract: Anomalous diffusion behavior can be observed in many single-particle (contained in crowded environments) tracking experimental data. Numerous models can be used to describe such data. In this paper, we focus on two common processes: fractional Brownian motion (fBm) and scaled Brownian motion (sBm). We proposed novel methods for sBm anomalous diffusion parameter estimation based on the autocovariance function (ACVF). Such a function, for centered Gaussian processes, allows its unique identification. The first e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…For Task 1 1D, we trained 12 models, each model corresponding to a batch of trajectory lengths: [10,20], [21,30], [31,40], [41,50] [36] generates trajectories with anomalous exponent α ∈ [0.05, 2) in intervals of 0.05. This means that 39 different alpha values can be generated, and there are five diffusion models for a total of 195 different kinds of trajectories.…”
Section: Model Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…For Task 1 1D, we trained 12 models, each model corresponding to a batch of trajectory lengths: [10,20], [21,30], [31,40], [41,50] [36] generates trajectories with anomalous exponent α ∈ [0.05, 2) in intervals of 0.05. This means that 39 different alpha values can be generated, and there are five diffusion models for a total of 195 different kinds of trajectories.…”
Section: Model Trainingmentioning
confidence: 99%
“…When regressing the anomalous diffusion exponent, the sensitivity of ML models to added noise in SBM trajectories warrants further study. Recently, Szarek [40] has encountered a similar lack in resiliency to noise using an RNN-based model, like UPV-Mat, HNU, and eduN models. It appears that the difficulty in working with SBM is an inherent characteristic of SBM trajectories, as opposed to the neural network architecture used for inference of α.…”
Section: Regression Of the Anomalous Diffusion Exponent (Task 1 1d)mentioning
confidence: 99%
“…Recurrent neural networks (RNN) have been used for inference of the anomalous diffusion exponent and for the classification of anomalous diffusion models [191][192][193][194] and changes between diffusion models [195]. Although questions exist with regard to their accuracy in handling long-time correlations.…”
Section: Neural Network For Time Series Analysismentioning
confidence: 99%
“…Szarek proposed a novel hybrid convolutional neural network model that uses a 1-to-1 method to predict the occurrence of four types of solar flares within 24 hours. The results showed that the prediction effect of this model was better than that of the traditional model [9]. Chea and Nam propose an optimal residual deep neural network and an efficient image preprocessing technique and apply the method to three eye disease classifications in currently available public datasets.…”
Section: Related Workmentioning
confidence: 99%
“…The algorithm has good recommendation performance Szarek [9] and Zheng et al [11] A new hybrid convolutional neural network model…”
Section: Multipopulation Collaborative Genetic Algorithm Based On Col...mentioning
confidence: 99%